2016
DOI: 10.1111/ijpo.12151
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in genes related to risk‐taking behaviours predicting body mass index trajectory among Mexican American adolescents

Abstract: Objectives Obesity is associated with multiple health problems and often originates in childhood. The purpose is to investigate the associations of genetic polymorphisms in genes related to risk-taking behaviors with body mass index (BMI) trajectory over adolescence among Mexican Americans. Methods This study included 1,229 Mexican American adolescents who participated in a large population-based cohort study in Houston, Texas. BMI data were obtained at baseline and two follow-ups. The median follow-up time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…For example, the effects of metabolic biomarkers 42 and environmental endocrine disruptors (EEDs) on children's BMI were not considered in our study. Second, because this analysis is based on cross-sectional data, we cannot make causal inferences.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…For example, the effects of metabolic biomarkers 42 and environmental endocrine disruptors (EEDs) on children's BMI were not considered in our study. Second, because this analysis is based on cross-sectional data, we cannot make causal inferences.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Recent studies suggest that genetic effects on obesity‐related phenotypes, like body mass index (BMI), may differ across life stages . To date, few genetic studies have focused on the effects of genetics across childhood , or Hispanic/Latinos , including Chileans, although they shoulder a high burden of obesity. These observations highlight the need to characterize the relevance of established genetic loci from infancy into adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that HTR2A agonist could increase lipid accumulation and 5-HT suppress lipolysis in 3T3-L1 adipocytes and a genetic variant in HTR2A associated with obesity [ 6 , 7 ]. In this research, HTR2A was upregulated in Day-4 and Day-9 compared to Day-0, so it was chosen for functional analyses.…”
Section: Resultsmentioning
confidence: 99%
“…HTR2A agonist treatment increased lipid accumulation and 5-HT suppressed lipolysis using 3T3-L1 adipocytes [ 6 ]. It has been identified as a genetic variant, namely, rs17069005 in HTR2A gene associated with obesity at last follow-up [ 7 ], but the role of HTR2A in mediating the effects on cattle adipocyte differentiation remains unexplored.…”
Section: Introductionmentioning
confidence: 99%